Counter-Radicalization Education Design as a Mitigation Strategy for Terrorism Among University Students - Nur Chanifah (Ambarsa : Jurnal Pendidikan Islam, 2026)
This research addresses the critical issue of radicalism within institutions of higher learning, focusing on Brawijaya University as a representative context where the phenomenon has reached alarming levels. Universities, as traditional incubators for the nation’s future leaders, are paradoxically being targeted by radical groups who use academic settings to disseminate extreme ideologies and broaden their organizational networks. This study aims to examine and formulate a comprehensive educational design to counteract radicalism within the university environment. Employing an empirical research methodology with a case study approach, data were gathered through in-depth interviews, systematic observations, and document analysis. The sample was selected by purposive and snowball sampling techniques to capture the perspectives of stakeholders most deeply affected by and involved in countering radicalism. The findings demonstrate that the counterradicalism educational model is characterized by its integration across multiple domains: curricular activities, supporting classes, extra-curricular initiatives, and the development of campus culture that fosters critical thinking, inclusivity, and tolerance. The study highlights the importance of a holistic and multifaceted approach, suggesting that long-term resilience against radicalism requires not only policy but also the ongoing engagement of the academic community through continuous educational intervention and proactive campus practices.